2019
DOI: 10.1007/s42452-019-0193-1
|View full text |Cite
|
Sign up to set email alerts
|

Environmental impact of the production of graphene oxide and reduced graphene oxide

Abstract: Reduced graphene oxide (rGO) is widely seen as the most promising route for the low-cost mass production of graphene for many applications ranging from ultrathin electrodes to structural nanocomposites. The Hummers and Marcano methods are the two most successful approaches for producing high-performance rGO, but have been criticized for producing toxic emissions. We have applied life cycle assessment methodology to evaluate the environmental impacts of both production routes for GO and rGO in the context of ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(39 citation statements)
references
References 67 publications
0
35
0
4
Order By: Relevance
“…All studies included in this section reported direct contributions from the production of GRMs, however, the system boundaries varied from 'cradle to gate' , [188,[195][196][197][198][199][200][201] 'cradle to installation' [202] and 'cradle to grave' [189]. The functional unit varied across these studies, with the large majority defined in terms of mass, e.g.…”
Section: Environmental Impacts Of Graphene-related Materials Producti...mentioning
confidence: 99%
“…All studies included in this section reported direct contributions from the production of GRMs, however, the system boundaries varied from 'cradle to gate' , [188,[195][196][197][198][199][200][201] 'cradle to installation' [202] and 'cradle to grave' [189]. The functional unit varied across these studies, with the large majority defined in terms of mass, e.g.…”
Section: Environmental Impacts Of Graphene-related Materials Producti...mentioning
confidence: 99%
“…The utilisation of strong chemicals in most graphene materials production methods remains a demanding challenge to the environment. For instance, the use of H2SO4 and hydrazine in GO and rGO synthesis have been widely criticised as these reagents poses serious ecological threat to both humans, terrestrial and aquatic environment, thus, could trigger freshwater eco-toxicity, cancer effect on humans, as well as NOx emissions [180]. In addition, the utilisation of organic solvents such as sodium dodecylsulphate (SDS) and sodium dodecylbenzenesulphonate (SDBS) in FLG/GNPs production [151], [156], [160] remain a possible cause for human [181] and environmental concern.…”
Section: Toxicity and Environmental Impact Of Graphene Materialsmentioning
confidence: 99%
“…In addition, recent cytotoxicity study (conducted via both in vitro and in vivo) on G-WBEC utilising FLG/Natural rubber (FLG-C-NR) nanocomposite revealed that graphene incorporation within the NR matrix do not compromise its biocompatibility, as no sign of toxicity, nor skin irritation were observed for up to 48 hours exposure [188]. However, majority of the available literature results suggests that graphene toxicity (as well as its susceptible environmental effects) is largely attributable to the overall nature of the surface chemistry (functionalised sites, especially the reactive oxygen species dominant in the derivatives such as GO), particle size, number of layers, concentration of the graphene material [189], [190] and the processing techniques employed in the graphene production [180].…”
Section: Toxicity and Environmental Impact Of Graphene Materialsmentioning
confidence: 99%
“…The so far reported works indicate that GO is advantageous for its composites' mechanical properties compared to pristine graphene [26]. However, the known methods to prepare the GO include strong chemicals (nitric or sulfur acids and potassium chlorate) [27] and produce noxious emissions [28]. In contrast, the multilayer graphene or graphene nanoplatelets (GnPs, >8 carbon layers) [29] can be directly prepared by liquid-phase exfoliation (in organic solvents, ionic liquids or water/surfactant) in large quantities [30,31], are inexpensive (<2 $/gram) [32,33], and therefore, would be ideal fillers for the improvement of mechanical and thermal properties of PEEK nanocomposites.…”
Section: Introductionmentioning
confidence: 99%